The use of laser therapy as an alternative in the treatment of pressure injuries: Integrative review (Research, Society and Development, 2024)
Pressure Injury is characterized by skin damage and soft tissue due to prolonged or intense pressure, resulting in ischemic lesions. The present study aimed to evaluate and synthesize the evidence about laser therapy's effectiveness in pressure treatment of injuries. It was an integrative literature review conducted in March 2024 using SciELO, VHL, PubMed, and CAPES Journals. Laser therapy is considered a therapeutic modality based on the laser application of light directly to the lesion area, resulting in analgesic, anti-inflammatory, and wound-healing effects, having biochemical, bioelectric, and bioenergetic effects. At the end of the study, it was observed that laser therapy used in pressure treatment of injuries presented significantly positive results, providing several benefits to patients. Laser therapy has proven to be a highly viable non-invasive alternative for injury management, standing out for its therapeutic efficacy.